Carbon and Nitrogen Stocks Under Different Land-Use in the Paraopeba River Basin-MG Before the Corrégo do Feijão Dam Burst - da Silva, Libério Junio; de Carvalho Vicente, Murilo; Rodriguez Lozada, Jorge; Almeida Durães, Débora; Borges Baldotto, Lílian Estrela; da Silva, Demétrius David; Machado Viana, Maria Celuta; Altoé Baldotto, Marihus (Revista Ceres, 2022)
Soil attributes can provide indicators for the management and conservation of natural and agrarian ecosystems. This study was carried out before the rupture of the Córrego do Feijão dam and aimed to evaluate and quantify the stocks of carbon, nitrogen and the C/N ratio in soils around the Paraopeba-MG river basin in five regions corresponding to the high, middle, and low river course, considering three usage factors: forest, pasture, and Shrubbery forest, correlating them with the chemical and physical properties of the soil, aiming at the interpretation of past use, to obtain management and conservation strategies for ecosystems. The results indicate a significant variation in carbon and nitrogen stocks with an increase in the 20-40 cm layer. Concerning the type of use, the forest system was the most efficient in accumulating carbon. About to site, the regions of Brumadinho and Fortuna de Minas showed similarities in the incorporation of carbon in the soil, differing from the regions of Jeceaba, Florestal, and Três Marias. There was a close correlation between stocks and the chemical and physical properties of the soil, making it possible to assess the quality of the soils in the study regions in terms of structure and fertility.